Biotechnological sovereignty is not a mere nationalist concept, it is a necessity for Colombia and Latin America - Camilo Guzman; Salim Mattar; Nelson Alvis-Guzman; Fernando De la Hoz; Edgar Arias (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: During the pandemic, Latin American countries suffered the collapse of their health systems. This was caused by the high demand for care of patients infected with SARS-CoV-2, which was added to the care of patients with other diseases. The significant increase in demand for health services caused medical and laboratory supplies to decline rapidly. The COVID-19 pandemic exacerbated a health crisis in several developing countries, mainly caused by insufficient systematic policies for integrating scientific knowledge. The current Colombian government must formulate a Biotechnological or Biosecurity Sovereignty Law that guarantees scientific autonomy, ensuring that Colombia is self-sufficient in Science, Technology, and Innovation. Colombian government should also focus on establishing and developing pharmaceutical chemical production by acquiring active chemical ingredients from other countries. This strategy could reduce the production costs and final prices of medicines, as well as generate high-level employment and wealth for the country. In this way, the Colombian government could prevent shortage of essential medicines and excessive price increases by commercial intermediation. In conclusion, the manuscript focuses on the lack of biotechnological sovereignty in Colombia. We propose a model of a Latin American Science and Technology ecosystem to achieve biotechnological sovereignty via state funding of research, strengthening universities, and fostering participation among private companies and Ministries of Science, Education, Trade, and Health. Scientific autonomy based on innovative processes that strengthen biotechnological independence can contribute to the economy by generating gross added value, creating high-quality employment, and facilitating the appropriation and social dissemination of knowledge, and cost reduction.